Theory and trauma - Biti, Vladimir (Primerjalna književnost, 2009)
This article questions the cosmopolitan spirit of modern literary theory in the context of its colonial aspirations.
Keywords: literarna teorija; literary theory; kolonializem; kozmopolitizem; kulturni imperializem